Perspektif Pelanggaran Perjanjian Utang: Pengujian Akrual dan Pilihan Metode Akuntansi - Prihat Assih (Jurnal Akuntansi dan Bisnis, 2004)
Debt covenant usually is limited by accounting number and violation of it will cause the firm bear a cost. Such cost can be a penalty, that determined by creditors. The firm violate public debt covenant, so it will downgrade the obligation rating. The high cost of it drive the manager tends to hinder the violation. Result of many researches show that the firms tend to choose accounting method to increase earning when they near to debt covenant violation.